Recent Patents of microRNAs as Biomarkers for Breast, Leukemia, Prostate and Cervical Cancers - M. ElHefnawi, Mahmoud; M. Ibrahim, Sahar; M. Ibrahim, Dina (Recent Patents on Biomarkers, 2013)
MicroRNAs (miRNAs) are a class of endogenously expressed, small noncoding RNAs, which play a crucial role in regulating different cellular processes. They are emerging as a new class of cancer biomarkers due to their deregulation and their stability in formalin-fixed tissue, blood and urine, making them easy and non-invasive biomarkers. In this review, we summarize some current knowledge about the potential use of miRNAs as biomarkers for ductal breast carcinomas, acute myeloid leukemia, prostate and cervical cancers highlighting some recent patents on discovery of miRNAs as novel biomarkers for those four cancers. miRNAs have been found out as circulating biomarkers for breast, acute myeloid leukemia and prostate cancers, as well as urine biomarkers for prostate, and only tissue biomarkers for cervical cancers. Some miRNAs are commonly deregulated in several cancer types (e.g., miR-34a, miR-182) but only few are type specific, offering an accurate biomarker for a particular cancer. In addition, miRNAs can help in recognizing certain cancers subtypes, for example, there are 12 down-regulated and 3 up-regulated miRNAs for the diagnosis of HER+ve breast cancer subtype, while there are 2 down-regulated miRNAs and 11 up-regulated miRNAs for HER-ve. For cancer staging, miRNAs were found to be a useful tool, in breast and prostate cancers, giving accurate indication for the stage and grade of cancer. Moreover, miRNAs serve in prognosis of acute myeloid leukemia and prostate cancers. Thus, miRNA expression in different body sites and fluids could serve as a useful diagnostic and prognostic biomarker for different cancers that should be expanded upon for future improvements in this sector.
Keywords: miRNA patents